2021
DOI: 10.1021/acs.jpcc.1c02767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phase Transition on the Thermal Transport in Isoreticular DUT Materials

Abstract: Soft porous crystals (SPCs) or flexible metal–organic frameworks have great potential applications in gas storage and separation, in which SPCs can undergo phase transition due to external stimuli. Thus, understanding the effect of phase transition on the thermal transport in SPCs becomes extremely crucial because the latent heat generated in aforementioned applications is needed to be effectively removed. In this paper, taking the isorecticular DUT series as an example, the thermal transport property of SPCs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 67 publications
(139 reference statements)
2
10
0
Order By: Relevance
“…Based on systematic modifications of simple model systems, it was suggested that the thermal conductivity is proportional to the inverse pore crosssectional area [45]. A strong correlation between pore size and thermal conductivity was indeed found also for actual MOFs [19,46]. Different heat transport pathways due to different MOF topologies modify this simple picture [43,45].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on systematic modifications of simple model systems, it was suggested that the thermal conductivity is proportional to the inverse pore crosssectional area [45]. A strong correlation between pore size and thermal conductivity was indeed found also for actual MOFs [19,46]. Different heat transport pathways due to different MOF topologies modify this simple picture [43,45].…”
Section: Introductionmentioning
confidence: 98%
“…The situation is further complicated by flexible MOFs, which undergo phase transitions that can change their pore sizes. A transition to more narrow pores like, for example, those found in MIL-53 has, indeed, lead to an increased thermal conductivity [46,47], while for systematically modified model systems it was shown that a change in the linker inclination angle reduces heat transport [48]. Interestingly, the strong impact of the pore size can lead to a situation where a disordered but denser phase of a MOF displays an increased thermal conductivity compared to its ordered counterpart [38,49].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, due to their ultra-high porosity and structural tunability, metal–organic frameworks (MOFs) have shown great potential in various applications, such as gas storage and separation, water harvesting, electronic devices, and heterogeneous catalysis . Lattice thermal conductivity is a critical parameter for MOFs in the context of thermal energy conversion, thermal management, and thermal stability and has attracted extensive experimental and theoretical studies.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in the results could be partially attributed to the different interatomic potentials used in different works, but there are two other possible causes. On the one hand, the heat current as implemented in the lammps package used in most of the previous EMD simulations ,, ,, was incorrect for many-body potentials, which could lead to significantly reduced thermal conductivity and phonon MFPs in systems with low-dimensional features . On the other hand, it is often assumed that a supercell with 2 × 2 × 2 conventional cells is sufficient to obtain convergent results in EMD simulations, ,,,, which is not necessarily valid.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the understanding of thermal transport properties of nanoporous materials, the focus has mainly been limited to MOFs and zeolites. ,,, Zeolites generally have higher thermal conductivities due to their relatively higher mass densities as shown in Figure . For MOFs, most of the studies generally report very low thermal conductivities (∼0.3 W m –1 K –1 ), which has mostly been attributed to the short mean free paths of the vibrational energy carriers resulting from their porous structures.…”
mentioning
confidence: 99%